Penggunaan Jasa Debt Collector Dalam Penagihan Pembiayaan Konsumen Oleh Pt Home Credit Indonesia Pekanbaru - Hapsi, Ellian Fadly; Lestari, Rika; Putra, Setia (Jurnal Ilmiah Wahana Pendidikan, 2025)
In consumer financing, it is often the case that the agreed agreement is defaulted by the consumer which results in the creditor's rights not being fulfilled so that the creditor makes collections using other parties, namely Debt Collector. PT Home Credit Indonesia Pekanbaru uses Debt Collectors in terms of collections made to debtors in the event of default or late payment. In this case, PT Home Credit Indonesia has violated the collection regulations written in the Financial Services Authority Regulation Number 22 of 2023. Therefore, the research objectives of this thesis are first, the use of debt collector services in consumer financing collection by PT Home Credit Indonesia Pekanbaru. Second, the efforts made by consumers when there is a billing violation. The type of research used is sociological legal research with the research location located in the Pekanbaru City area. The population and sample are parties who are in the financing period. This research uses data sources in the form of primary and secondary data, and data collection techniques are carried out by means of questionnaires. From the results of the problem research, there are two main things that can be concluded. First, PT Home Credit Indonesia Pekanbaru uses debt collectors as proxies to collect debtors who have defaulted, and there are collection violations as written in the Financial Services Authority Regulation Number 22 of 2023 concerning Consumer and Community Protection in the Financial Services Sector. Second, legal efforts made by consumers can be made through litigation and out of court (non-litigation), many consumers refuse to make legal efforts because they do not have enough time and money and also do not know about legal efforts that can be made outside the court